In vitro Effects of Antimicrobial Agents on Planktonic and Biofilm Forms of Staphylococcus saprophyticus Isolated From Patients With Urinary Tract Infections - Martins, Katheryne Benini; Ferreira, Adriano Martison; Pereira, Valéria Cataneli; Pinheiro, Luiza; Oliveira, Adilson de; Cunha, Maria de Lourdes Ribeiro de Souza da (Frontiers in Microbiology, 2019)
Bacterial biofilms play an important role in urinary tract infections (UTIs), being responsible for persistent infections that lead to recurrences and relapses. Staphylococcus saprophyticus is one of the main etiological agents of UTIs; however, little is known about biofilm production in this species and especially its response to antimicrobial agents used for the treatment of UTIs when a biofilm is present. For this reason, the aim of this work was to evaluate the response of S. saprophyticus biofilms to five antimicrobial agents. Staphylococcus saprophyticus was evaluated for antimicrobial susceptibility in its planktonic form by means of minimum inhibitory concentration (MIC) and in biofilms by means of minimum inhibitory concentration in biofilm (MICB) against the following antimicrobial agents by the microdilution technique: vancomycin, oxacillin, trimethoprim/sulfamethoxazole, ciprofloxacin, and norfloxacin. Of the 169 S. saprophyticus studied, 119 produced a biofilm as demonstrated by the polystyrene plate adherence method. Biofilm cells of S. saprophyticus exhibited a considerable increase in MICB when compared to the planktonic forms, with an increase of more than 32 times in the MICB of some drugs. Some isolates switched from the category of susceptible in the planktonic condition to resistant in the biofilm state. Statistical analysis of the results showed a significant increase in MICB (p <0.0001) for all five drugs tested in the biofilm state compared to the planktonic form. Regarding determination of the minimum bactericidal concentration in biofilm (MBCB), there were isolates for which the minimum bactericidal concentration of all drugs was equal to or higher than the highest concentration tested.